Analisis Deiksis dalam Channel YouTube Satu Persen pada Daftar Putar “Manajemen Waktu” - Dhea Aulia Rodhiasari; Novi Fitriani; Regina Samosir; Almas Bari’atul Muna; Rania Nursifaturozaq Shafarina; Asep Purwo Yudi Utomo; Rossi Galih Kesuma (Pusat riset dan Inovasi Nasional, 2024)
The studies we took in this research are from the field of pragmatics. The pragmatics study in this research focuses on deictic analysis. Deixis is a part of pragmatics that discusses the expressions or context in a sentence. This research aims to analyze various types of deixis contained in the 'Time Management' video on the Satu Persen YouTube channel. This research was carried out using a qualitative approach, namely a method as a research procedure that produces descriptive data. The research techniques used to produce data are observation techniques, note-taking techniques, writing techniques, and listening techniques. In the analysis of deixis in a series of videos contained in the 'Time Management' playlist via the One Percent YouTube channel that we studied, five types of deixis can be found, namely persona deixis (first person singular, first person plural, second person singular, second person plural, third person singular), place deixis, time deixis (past, present, future), discourse deixis (anaphora, cataphora), and social deixis. Each type of deixis has its own function depending on its context. This research will be interesting for readers who have difficulty managing time.